Protein efficiency ratio in broiler fed hydrolyzed palm kernel meal-based rations using mannase and cellulase enzymes - Hermanto, Tri; Mairizal, Mairizal; Yusrizal, Yusrizal (Fakultas Peternakan Universitas Papua, 2024)
This research aims to see the effect of administering mannanase and cellulase enzymes in the hydrolysis of diets containing palm kernel meal on the protein efficiency ratio in broilers. This research used 200 DOC that were reared for 35 days with a research design in the form of a Completely Randomized Design with 5 treatments and 4 replications, namely P0 = basal ration, P1 = basal ration + 50 ml mannanase enzyme/Kg ration + 50 ml cellulase enzyme/Kg ration, P2 = basal ration + 50 ml mannanase enzyme/Kg ration + 100 ml cellulase enzyme/Kg ration, P3 = basal ration + 100 ml mannanase enzyme/Kg ration + 50 ml cellulase enzyme/Kg ration, P4 = basal ration + 100 ml mannanase enzyme/Kg ration + 100 ml cellulase enzyme/Kg ration. The variables observed in this study were ration consumption, protein consumption, body weight gain, and protein efficiency ratio. Data were analyzed using analysis of variance (ANOVA); if there was a real effect, then continued with the Duncan test. The results showed that giving rations based on palm kernel meal, which was hydrolyzed using cellulase and mannanase enzymes, had a significant effect (P<0.05) on ration consumption, protein consumption, and body weight gain but had no significant effect (P>0.05) on the ratio protein efficiency. It was concluded that providing a ration based on palm kernel meal hydrolyzed using mannanase and cellulase can be used in broiler chicken rations